20 years of economic corridors development: a bibliometric analysis. Issue 1 (1st January 2021) - Xu, Can; Yu, Deming; Yang, Hao; Yu, Shiyao
ABSTRACT: The focus of this paper aims to comprehensively analyze the global high-level scientific output of economic corridors. In this study, bibliometric method is utilized not only to help identify core collaboration networks among authors, institutions, countries, but also to characterize research hotspots and research frontiers. This research has found that the number of papers dealing with economic corridors has appeared a trend of sustained growth. The most prolific country and institution are China and Chinese Academy of Science, respectively. The core of the international author cooperation community has not yet been formed. Relevant literature mainly focuses on the field of Environmental Sciences & Ecology. The hotspots include "Ecological environment protection", "Economic development", "Transportation", "Resource utilization and saving" and "Belt and road initiative". Environmental protection is a frontier subject. This finding is helpful to a comprehensive understanding of the development trend of economic corridors study.